Fifth Five Year Plan (1974-79) Proposals of Chandigarh Administration - Planning Commission (Planning Commission, 1974)
Corbusier’s vision of Chandigarh envisaged its development as a predominantly administrative city, offering all amenities of life to the various sections of its population. This was based on a very imaginative area planning keeping in view the climatic conditions, habits of the people and the human and material resources. The concept of sectoral living, the classification of roads, the zoning plans, and the architectural controls were clearly defined to shape the larger concept of a city as a living, throbbing, viable organic body. The Master Plan was as much an effort at co-ordinated development as an attempt to take account of the imperative factors of ecology, so that living and working could be carried on in the most congenial environments.
Proposals of Chandigarh Administration Department of Finance Chandigarh Administration